Search for the rare decays B+→D(*)+KS0 - Aubert, B; Barate, R; Boutigny, D; Couderc, F; Karyotakis, Y; Lees, J; Poireau, V; Tisserand, V; Zghiche, A; Grauges, E; Palano, A; Pappagallo, M; et al. (2005)
We report on the search for the rare decays B+→D(*)+KS0 in approximately 226×106 Υ(4S)→BB̄ decays collected with the BABAR detector at the PEP-II asymmetric-energy B factory at SLAC. We do not observe any significant signal and we set 90% confidence-level upper limits on the branching fractions, B(B+→D+K0)<0.5×10-5 and B(B+→D*+K0)<0.9×10-5. © 2005 The American Physical Society.